TRPing the homeostatic alarm — Melanoma cells are selectively vulnerable to TRPML1 deletion. (December 2019) - Jung, Jewon; Venkatachalam, Kartik
Highlights: Recent study by Kasitinon et al. describe a role for TRPML1 in melanoma. Deletion of the channel results in toxic ERK and mTORC1 hyperactivation in melanoma. Perspective on TRPML1 function in cancer is provided. Abstract: To thrive in otherwise inhospitable conditions, cancer cells utilize endolysosomes to impose homeostatic control over cellular metabolism and growth. In a recent study, Kasitinon et al. demonstrate a requirement for the endolysosomal channel, TRPML1, in proliferation and survival of melanoma cells. This study adds to a growing list of cancers that exhibit selective vulnerability to the loss of TRPML1.